Recuperação espontânea, curso temporal e influência circadiana na habituação das respostas cardiovasculares ao estresse de restrição repetido em ratos - Santos, Carlos Eduardo dos (2020)
Stress is related to the development of several cardiovascular diseases. These diseases are related to morphofunctional changes that can be triggered by chronic exposure to aversive events. However, an important adaptive mechanism that seems to reduce morphofunctional changes and diseases is the progressive reduction in physiological responses upon repeated exposure to the same stressor stimulus, a phenomenon called habituation. Despite the relevance of the habituation process, the mechanisms related to this phenomenon are still poorly understood. Thus, the objectives of this study were: 1) to evaluate in male rats how many days of restraint stress are necessary for habituation to occur; 2) identify how many days of interruption of the repeated restraint stress protocol are necessary for the recovery of the habituated response (i.e., spontaneous recovery); and 3) to verify if the period of the day influences the magnitude of the habituation process in rats. We also evaluated the habituation of the corticosterone response to repeated restraint stress. We observed that the increase in serum corticosterone decreased during the stress of recovery period of the 10th session of restraint, when compared to the response of animals acutely stressed. The habituation of cardiovascular responses was identified as a faster return of heart rate (HR) and blood pressure (BP) to baseline values during the recovery period of the 10th restraint session. Habituation of HR and BP was still observed after 10 days of discontinuation of the repeated exposure to restraing stress. However, spontaneous recovery of both habituated responses was observed 20 days after the last session of repeated restraint exposure. Time course analysis revealed decreased HR values during the recovery period at the 3rd restraint session, with no further reduction at the 5th, 7th and 10th sessions. The decrease in BP response was identified at the 3rd and 5th sessions, while reduced response of the tail skin temperature was observed only at the 5th and 7th sessions. Regarding the time of day, habituation to the tachycardic response was identified when repeated restraint stress was performed on the morning and evening, but not in the afternoon. Together, these findings provide evidence of spontaneous recovery of the habituation of cardiovascular responses to repeated restraint stress. The results also indicate that cardiovascular habituation depends on the number of trials and the time of day.